PENGARUH PENERAPAN KEGIATAN PERMAINAN TRADISIONAL BOI-BOIAN TERHADAP MOTORIK KASAR ANAK USIA 4-5 TAHUN DI PAUD MITRA HANDAYANI PEKANBARU - Yuliana, Rika; Chairilsyah, Daviq; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study are as follows: 1) To determine the gross motor skills of children aged 4-5 years prior to the application of the traditional game activities in early childhood Boi-Boian Hand Partners Pekanbaru. 2) To determine the gross motor skills of children aged 4-5 years after the implementation of the activities of traditional games in early childhood Boi-Boian Hand Partners Pekanbaru. 3) To find out how high the level of influence the application of the traditional game activities Boi-Boian on gross motor skills of children aged 4-5 years in early childhood Mitra Hand Pekanbaru. The research sample is the child class A consisting of 15 children, consisted of 7 men and 8 women. Collecting data using observation and documentation. The data analysis technique used in this study is t test analysis techniques. From the results obtained with t = 11 767 means greater than ttable the significant level of 5% and at significant level of 1% (2.160 <11 767> 2.98). Thus, it means Ho is rejected. This means that there is significant influence between boi-Boian tradisioanl game against the gross motor skills of children aged 4-5 years in early childhood Mitra Hand Pekanbaru. From this study it can be concluded that the application of the boi-Boian tradisioanl game against the gross motor skills of children aged 4-5 years in early childhood Mitra Hand Pekanbaru. It can be seen that there is a difference in the form of an increase in gross motor skills children before treatment and after treatment and have the effect of 28.15%Keywords: application of the traditional game boi-Boian, gross motor skills children